Using dense Sentinel-2 time series to explore combined fire and drought impacts in eucalypt forests - Hislop, Samuel; Stone, Christine; Gibson, Rebecca K.; Roff, Adam; Choat, Brendan; Nolan, Rachael H.; Nguyen, Trung H.; Carnegie, Angus J. (Frontiers in Forests and Global Change, 2023)
Following one of the driest years on record, millions of hectares of forests in southeast Australia were burned in the 2019–2020 ‘Black Summer’ wildfires. In addition to the areas burned, drought related canopy collapse, dieback and tree mortality was widely observed. In this paper, we present a method to map canopy damage due to drought and fire across a large area. Sentinel-2 satellite imagery was used in a monthly time series to highlight areas of forest where the Normalized Burn Ratio index was significantly below a pre-disturbance ‘stable’ period. The stable period was defined as the three years prior to 2019 and the disturbance thresholds are based on bioregion specific standard deviations below pre-disturbance means. The novel methods enabled drought impacted forests to be identified, including those which were subsequently burned by wildfire. Across the 20 Mha of forests studied, 9.9 Mha (49%) fell below the disturbance threshold. Of that, 5.8 Mha was disturbed by fire and a further 4.1 Mha by drought outside of the fire extent. Within the fire extent, almost 0.9 Mha was identified as being significantly drought affected prior to being burned. An analysis of spectral recovery following substantial rainfall from February 2020 onwards indicates that most of the areas impacted by both drought and fire have similar rates of recovery to those impacted only by fire. There are some areas, however, where the combined effects of the ‘double disturbance’ appears to be hindering recovery. The methods presented here are easily transferrable and demonstrate an approach for monitoring forest disturbance at higher temporal and spatial scales than those typically used.